Excellent suppression of physiological myocardial FDG activity in patients with cardiac sarcoidosis. Issue 1 (25th October 2020) - Sankaran, Shyam S; Kyprianou, Katerina; Cherk, Martin H; Nadebaum, David P; Beech, Paul A; Khor, Robert; Zimmet, Hendrik; Hare, James L; Larby, Annabel; Yap, Kenneth SK; Barber, Thomas W
Abstract: Introduction: Suppression of physiological myocardial FDG activity is vital in patients undergoing PET/CT for assessment of known or suspected cardiac sarcoidosis. This study aims to evaluate the efficacy of physiological myocardial FDG suppression following a protocol change to a 24‐h high fat very low carbohydrate (HFVLC) diet and prolonged fast. Methods: A retrospective review of patients undergoing FDG PET/CT for the evaluation of cardiac sarcoidosis was performed. Prior to June‐2018, patients were prepared with a single very high‐fat low carbohydrate meal followed by a 12–18 h fast (group 1). After June‐2018, a protocol change was initiated with patients prepared with a HFVLC diet for 24‐h followed by a 12–18 h fast (group 2). Focal myocardial activity was classified as positive, absent activity as negative and diffuse/focal on diffuse activity as indeterminate. Results: A total of 94 FDG PET/CT scans were included with 46 scans in group 1 and 48 scans in group 2. Studies were classified as positive, negative or indeterminate in 25 (54%), 7 (15%) and 14 (30%) scans in group 1 and in 13 (27%), 33 (69%) and 2 (4%) scans in group 2, respectively. In scans classified as negative, myocardial FDG activity was less than mediastinal blood pool activity in 5/7 (71%) scans in group 1 and 33/33 (100%) scans in group 2. Conclusion: Excellent myocardial FDG suppression can be achieved using a 24‐h HFVLC diet and prolonged fast, resulting in a very low indeterminate scan rate in patients with known or suspected cardiac sarcoidosis.